Purification and Characterization of Native and Vaccine Candidate Mutant Enterotoxigenic Escherichia coli Heat-Stable Toxins - Govasli, Morten L. (Toxins (Basel), 2018)
Enterotoxigenic Escherichia coli (ETEC), which secretes the heat-stable toxin (ST) is among the four most important enteropathogens that cause moderate-to-severe diarrhea in children in low- and middle-income countries. ST is an intestinal molecular antagonist causing diarrhea and hence an attractive vaccine target. A non-toxic and safe ST vaccine should include one or more detoxifying mutations, and rigorous characterization of such mutants requires structurally intact peptides. To this end, we established a system for purification of ST and ST mutants by fusing the sequence encoding the mature ST peptide to the disulfide isomerase DsbC. A Tobacco Etch Virus protease cleavage site facilitates the proteolytic release of free ST with no additional residues. The purified ST peptides have the expected molecular masses, the correct number of disulfide bridges, and have biological activities and antigenic properties comparable to ST isolated from ETEC. We also show that free DsbC can assist in refolding denatured and misfolded ST in vitro. Finally, we demonstrate that the purification system can be used to produce ST mutants with an intact neutralizing epitope, that two single mutations, L9S and A14T, reduce toxicity more than 100-fold, and that the L9S/A14T double mutant has no measurable residual toxicity.